Zinc accelerates Dengue Virus Type 2-Induced Aapoptosis in Vero Cells - Shafee, N.; AbuBakar, Sazaly (2002)
Dengue virus type 2 (DENV-2) infection induced apoptotic cellular DNA fragmentation in Vero cells within 8 days of infection. The addition of high concentrations of extracellular Zn2+ but not Ca2+, Mg2+ or Mn2+ to the cell culture medium hastened the detection of apoptosis to within 4 h after infection. No apoptotic cellular DNA fragmentation was detected in the cell culture treated with Zn2+ alone or infected with heat- or ultraviolet light-inactivated DENV-2 in the presence of Zn2+. These results suggest that (i) apoptosis is induced in African green monkey kidney cells infected with live DENV-2 and (ii) the addition of high extracellular Zn2+ accelerates detection of apoptosis in the DENV-2-infected cells. (C) 2002 Published by Elsevier Science B.V. on behalf of the Federation of European Biochemical Societies.